SIFAT FISIKA MEKANIKA BRIKET ARANG KAYU LIMBAH INDUSTRI KAYU LAPIS DAN LIMBAH KAYU HTI : Alpian dan Wahyu Supriyati - JHT, Admin (Jurnal Hutan Tropika, 2016)
ABSTRACT Wood waste is biomass waste from wood cutting and the waste of the production process of the wood processing industry. Waste can be seen as a form of output side of a production process which often do not have economic value (unuse). Charcoal briquettes can be developed the waste biomass utility. This study aims is to determine the physical-mhanical properties of charcoal briquettes produced from the raw material of wood charcoal of plywood industrial waste (waste stripping finir) and waste of indutry plantation forest (HTI) from top/end section. Physical-mechanical properties of charcoal briquettes of this research qualify to the general requirements of the charcoal Indonesia quality (SNI 01-6235-2000). Keynotes: Charcoal briquette, waste, wood